Effect of Multiple Stresses (Thermal, Nutritional, and Walking Stress) on the Reproductive Performance of Malpura Ewes - V. Sejian; V. P. Maurya; K. Kumar; S. M. K. Naqvi (Veterinary Medicine International)
A study was conducted to assess the effect of multiple stresses (thermal, nutritional, and walking stress) on the reproductive performance of Malpura ewes. The study was conducted for a period of 35 days covering two estrous cycles during summer season (April-May). The ewes were randomly allocated into two groups of twelve animals each namely, GI (𝑛=12; Control), and GII (𝑛=12; Multiple stresses). GI ewes were maintained in the shed, while GII ewes were subjected to multiple stresses (thermal, nutritional, and walking stress). The estrus % differed significantly (𝑃<0.05) between the groups. Estrus duration also showed similar trend to that of estrus %. Both conception and lambing rate also differed significantly (𝑃<0.05) between the control and multiple-stress group. In addition plasma estradiol and progesterone also showed significant difference between the groups. The study proved the detrimental effects of multiple-stresses on various reproductive parameters studied. Hence it is very pertinent to conclude that when two or more than two stressors occur simultaneously, the total impact may be severe on reproductive functions of the animals.